Association between excess peripheral, central and general adiposity and different contexts of physical activity among adolescents from Southern Brazil - Leandro Narciso Santiago; Priscila Custódio Martins; Diego Augusto Santos Silva (Universidade Estadual de Maringá, 2024)
The aim of this study was to investigate the association between excess peripheral, central and general adiposity and different contexts of physical activity (Physical Education classes, school recess, commuting, leisure time and participation in sports teams) in adolescents from Southern Brazil. Across-sectional study was developed with 1.132 adolescents (16.50 ± 1.14 years) of both sexes. Peripheral adiposity (triceps skinfold) and central adiposity (subscapular skinfold) were classified as high based on the 90th percentile of the Centers for Disease Control and Prevention reference distribution. For excess general adiposity, triceps and subscapular skinfold thicknesses above the 90th percentile were simultaneously considered. The different contexts of physical activity were obtained through self-reported questionnaire. Covariates were: age, economic level, eating habits measured through self-administered questionnaire and sexual maturation (self-reported, following Tanner's procedures). Binary logistic regression was used with significance level < 0.05. Male adolescents little active during leisure time were 2.25 (95%CI: 1.17; 4.50) times more likely of having excess peripheral adiposity, 3.10 (95%CI: 1.56; 6.13) times more likely of having excess central adiposity and 2.38 (95% CI: 1.08; 5.26) times more likely of having general adiposity when compared to peers active during leisure time. For female adolescents, no context of physical activity was associated with excess peripheral, central and general adiposity. Male adolescents little active during leisure time are more likely of having excess peripheral, central and general adiposity. For female adolescents, no context of physical activity was associated with excess peripheral, central and general adiposity.